2013
DOI: 10.21082/ijas.v13n1.2012.p18-26
|View full text |Cite
|
Sign up to set email alerts
|

POTENCY OF PREDATOR (Menochilus sexmaculatus) AUGMENTATION FOR WHITE FLY (Bemisia tabaci) MANAGEMENT AND ITS EFFECT ON GEMINI VIRUS INFESTATION ON TOMATO

Abstract: Bemisia tabaci (Genn.) (Homoptera: Aleyrodidae) is one of the most serious pests on tomato. It is mainly controlled by chemical means, requiring some 25 sprays during the average growing season. The extensive and repeated use of insecticides has disrupted the natural balance between this pest and its natural enemies. In this study, Menochilus sexmaculatus F. was evaluated as a possible biological control agent of B. tabaci and its effect on gemini virus infestation. The study was conducted at the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Menochilus sexmaculatus was most commonly found as a predator of S. frugiperda in this study because this beetle has a wide range of prey [17]. Apart from aphids, M. sexmaculatus is also known to prey on the whitefly Bemisia tabaci Setiawati, et al [24] and Diaphorina citri [25]. Among the prey that has been mentioned, M. sexmaculatus has a preference for Aphis gossypii.…”
Section: Abundance Of Insect Predator Of S Frugiperda In Sleman and G...mentioning
confidence: 94%
“…Menochilus sexmaculatus was most commonly found as a predator of S. frugiperda in this study because this beetle has a wide range of prey [17]. Apart from aphids, M. sexmaculatus is also known to prey on the whitefly Bemisia tabaci Setiawati, et al [24] and Diaphorina citri [25]. Among the prey that has been mentioned, M. sexmaculatus has a preference for Aphis gossypii.…”
Section: Abundance Of Insect Predator Of S Frugiperda In Sleman and G...mentioning
confidence: 94%
“…Rodrı ´guez-Lo ´pez et al [70] observed that the primary and secondary spread of TYLCV by viruliferous whiteflies in greenhouse studies to their acylsugar-accumulating tomato line decreased and was dependent on the time of year and concluded that acylsugarmediated resistance in the lines tested was optimal in warm and dry growing regions and not likely to provide adequate virus protection for younger plant stages. Setiawati et al [79] evaluated several tomato varieties in a field trial and observed variation in whitefly abundance that was correlated with trichome abundance, but they did not evaluate the amount of acylsugars accumulated or acylsugar chemistry. Marchant et al [72] evaluated some of the same lines used in our study using lab assays, finding negative impacts of in planta produced acylsugars on whiteflies and a negative correlation between acylsugars and whitefly acquisition as well as…”
Section: Plos Onementioning
confidence: 99%
“…• The presence in number of the glandular trichomes in tomatoes have been associated with the reducing the number of the whitefly damaging the tomato plant (Setiawati et al, 2009).…”
Section: Host Plant Resistancementioning
confidence: 99%